Empowerment of Coastal Communities as a Component of Sea Dimension Reserves in Support of Indonesia's Maritime Defense - Amanda Mary Kartika Palar; Beni Rudiawan; Buddy Suseto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Geographically, Indonesia has the longest coastline in both Asia and the world. This makes coastal areas vulnerable to various crimes, especially those using the sea and the coast as an alternative. Therefore, it is necessary to strengthen through community empowerment in coastal areas as part of the duties of the Indonesian Navy as written in RI Law Number 34 of 2004 Article 9 (e), which is to maximize its role in empowering maritime defense areas. The purpose of this study is to analyze the empowerment of coastal communities carried out by the Indonesian Navy in supporting Indonesia's maritime defense strategy. The research method used is descriptive qualitative method. The result of this research is that by empowering coastal communities as Komcad Matra Laut, in addition to increasing Indonesia's maritime defense, it can also improve welfare and human resources in coastal areas. Defense and the economy support each other so that peace and prosperity can be created for the Indonesian people. Suggestions from this study are that synergy between the Indonesian Navy and the City and Provincial Governments is needed in empowering coastal communities as Marine Command Command in supporting Indonesia's maritime defense.